Leveraging students prewriting: Translanguaging in Indonesian higher education context - Retnowaty, Retnowaty (Studies in English Language and Education, 2025)
Advertisement sells fantasy more than it sells products. Through its slogan, an EFL students in Indonesia often encounter difficulties developing ideas because of their limited English proficiency, which can hinder their writing development. This study examined how translanguaging enhanced idea generation among EFL students in Indonesian higher education during the prewriting stage by utilizing their diverse linguistic repertoires to improve communication. Through classroom ethnography and the Multimodal Conversation Analysis framework, the research explored how students employed their linguistic and multimodal resources to develop ideas, facilitate communication and collaboration, and support creative expression and problem-solving. Data were collected through video recordings of student interactions and written artifacts produced during the prewriting session. The findings revealed that EFL students effectively coordinated verbal and nonverbal modes to co-construct meaning, creatively convey concepts, and enrich idea expression during prewriting activities. The study also uncovered that translanguaging occurred when students creatively co-construct information, reflect their identities, produce meaning flexibly, impact each other's language usage, and communicate multimodally. This study highlighted the importance of recognizing and valuing students' linguistic and cultural backgrounds and their multimodal competencies in developing inclusive and equitable learning environments that foster academic writing success. By embracing students' holistic communicative repertoires, translanguaging and multimodal practices can create a conducive atmosphere for engaging and memorable multilingual learning experiences.